Pendekatan Manajemen Program dengan Menggunakan Maeutic Machine dalam Percepatan Pencapaian Proyek Strategis Nasional RPJMN 2015-2019 - Wahyu, Marsellinus Bachtiar (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
In the period of 2014-2019, the implementation of infrastructure projects was encouraged everywhere with the aim of national connectivity and the smooth flow of national goods. This initiative has an impact on the welfare of the community in the form of poverty alleviation, reducing inequality in the development of Western and Eastern Indonesia, job creation and national competitiveness. Evaluation of the implementation of infrastructure projects shows in general the green report cards for project accomplishments, but on the other hand there are still inherent problems in the implementation in the field, especially regarding land acquisition, overlapping regulations, financing and conflicts of interest. Management of infrastructure projects requires a project management system that is different from conventional project management. In the framework of program management, this national program is managed in coordination across ministries, institutions with the aim of accelerating completion. The purpose of this paper is to describe the Meutic Machine approach as an alternative way of working in program management in the context of accelerating the achievement of national strategic projects in the 2014-2019 RPJMN. The Maeutic Machine Approach aims to question the potential risks to the achievement of a project with a procedural cycle. With this analytical engine coupled with coordination, monitoring and evaluation, it is expected that the implementation of portfolio projects can run well. The Meutic Machine approach is focused on questioning the possibilities systematically, and this is an advantage of the Maeutic Machine.